Development of a lateral flow immunoassay strip for rapid detection of IgG antibody against SARS-CoV-2 virus - Wen, Tian; Huang, Chao; Shi, Feng-Juan; Zeng, Xiao-Yan; Lu, Tian; Ding, Shou-Nian; Jiao, Yong-Jun (Analyst (London), 2020)
The ongoing worldwide SARS-CoV-2 epidemic clearly has a tremendous influence on public health. Molecular detection based on oral swabs was used for confirmation of SARS-CoV-2 infection. However, high false negative rates were reported. We describe here the development of a point-of-care (POC) serological assay for the detection of IgG antibody against SARS-CoV-2. The principle of a lateral flow immunoassay strip (LFIAs) consists of fixing SARS-CoV-2 nucleocapsid protein to the surface of the strip and coupling anti-human IgG with colloidal gold nanoparticles (Au NPs). A series of parameters of this method were optimized, including the concentration of coating antigen, BSA blocking concentration and pH value for conjugation. The entire detection process took 15-20 min with a volume of 80 μL of the analyte solution containing 10 μL of serum and 70 μL sample diluent. The performance of the established assay was evaluated using serum samples of the clinically diagnosed cases of Coronavirus Disease 2019 (COVID-19). Our results indicated that the LFIAs for SARS-CoV-2 had satisfactory stability and reproducibility. As a result, our fast and easy LFIAs could provide a preliminary test result for physicians to make the correct diagnosis of SARS-CoV-2 infections along with alternative testing methods and clinical findings, as well as seroprevalence determination, especially in low-resource countries. Rapid and simple LFIA strips based on Au NPs provide a preliminary test result for physicians to make the correct diagnosis of SARS-CoV-2 infections along with alternative testing methods.